Doom-Fugues: Their centrifugal/centripetal potential. - Fitch, Toby (Overland, 2025)
The article focuses on the idea of "doom-fugues," arguing that contemporary poetry mirrors the experience of doomscrolling through fugue-like forms that oscillate between movement and containment. Topics include the comparison of poetry and doomscrolling as immersive cognitive states, the use of centripetal and centrifugal poetic techniques to represent digital overload, and close readings of Australian poets whose work captures precarity, technology, and fractured subjectivity.